On the dynamics of the Greek twin deficits: Empirical evidence over the period 1960 - 2007 - Pantelidis Panagiotis; Trachanas Emmanouil; Athanasenas L. Athanasios; Katrakilidis Constantinos (International Journal of Economic Sciences and Applied Research, 2009)
One of the most important open macroeconomic issues, during the current global economic recession, concerns the sustainability of persistent budget and trade deficits as well as possible interactions between them. These deficits are most crucial due to severe debt servicing costs, faced by today's economies despite their development level. This paper presents time series evidence over the period 1960 up to 2007, using data of the Greek Economy. Our results confirm weak sustainability of both deficits and evidence in favor of the Keynesian rationale regarding the twin deficits hypothesis.
Keywords: C22; F32; F41; H62; 330; budget and trade deficits; sustainability; twin deficits hypothesis; cointegration; Greek economy (1960-2007)